Laughs and Jokes in Assisted Reproductive Technologies: Quantitative and Qualitative Analysis of Video-Recorded Doctor-Couple Visits - Poli, Silvia; Borghi, Lidia; De Stasio, Martina; Leone, Daniela; Vegni, Elena (Frontiers in Psychology, 2021)
Purpose: To explore the characteristics of the use of laughs and jokes during doctor-couple assisted reproductive technology (ART) visits. Methods: 75 videotaped doctor-couple ART visits were analysed and transcribed in order to: 1) quantify laugh and jokes, describing the contribution of doctors and couples and identifying the timing of appearance; 2) explore the topic of laughs and jokes with qualitative thematic analysis. Results: On average, each visit contained 17.1 utterances of laughs and jokes. Patients contributed for 64.7% of utterances recorded. Doctor (40.6%) and women (40%) introduced the majority of laughs and jokes. Visits with female physicians had significantly more laughs and jokes than visits with male doctors; no differences were found considering physicians’ age and years of experience, cause of infertility and prognosis. Laughs and jokes were mainly recorded during history taking and information giving. Four core themes were identified, regarding the topic of laughs and jokes: health status, infertility treatment, organizational aspects, doctor-patient interaction. Conclusion: Laughs and jokes are common in doctor-couple ART visits and are frequently used during the dialogue, covering a wide range of topics. Results seem to show that laughs and jokes are related to doctor’s personal characteristics (like gender), while are not associated with infertility aspects. Given the complexity of this communicative category, further studies are needed to explore the functions and the effects of laugh and jokes.